Existence of Female Journalists Wearing Jilbab in the Television Media Jakarta - Qisthy Rabathy; Elly Komala; Yanti Susila Trisnawati; Nik Fadlah (Future Science, 2021)
Female who wear jilbab is now choosing journalists as a job. Journalists are a job which exists in the middle of the community who is assigned to provide information or news to the public. This is a very heavy profession and not everyone can do this profession. Uncertain journalist working hours added with various difficulties and obstacles in this profession make this profession identified as a male profession. This becomes a challenge for journalists wearing jilbab who choose this job as their profession